واقع المحددات النفسية في انتقاء ناشئي ألعاب القوى من وجهة نظر المكونين - قاطر عدنان (My University, 2023)
Abstract The psychological determinants nowadays are considered an important and indispensable part of the selection process, especially in domain of sports.Thus, all the coaches and supervisors who select the players must be well informed of the most important psychological determinants and consider them during the above mentioned process so that it can be well executed. Our study aims to determine the reality of the adoption of psychological determinants in the process of selecting juniors in athletics. We initiate the study at hand by raising the following problem: do coaches and supervisors possess the required knowledge, in the sport of athletics, concerning the most important psychological determinant ? and to what extent do they put them to use? Hence, we provided a hypothesis as a preliminaryanswer to this question, stated as follows: "coaches and supervisors possess an acceptable level of knowledge of the various studied and approved psychological determinantsin the selection process." To investigate the stated objective, a sample estimated at 33 coaches from the South-East Regional Association for Athletics were served surveys, in which the descriptive analytical approach was adopted. Results reached show that the level of familiarity with the psychological determinants and their consideration by the coaches and supervisors in the selection process for juniors in athletics is somewhat acceptable ......................................................................................................الملخص ....................................................................... إن المحددات النفسية في وقتنا الحالي تعتبر جزءا هاما لا يتجزأ من عملية الانتقاء، خاصة في المجال الرياضي، حيث أن كل المؤطرين والمدربين الذين يقومون بانتقاء اللاعبين يجب أن يكونوا على اطلاع جيد على أهم المحددات النفسية ومراعين لها خلال العملية لتتم على أحسن وجه. تهدف دراستنا إلى تحديد واقع اعتماد المحددات النفسية في عملية انتقاء الناشئين في ألعاب القوى، حيث منطلق دراستنا هو طرح الإشكالية التالية: هل هناك اطلاع للمدربين والمؤطرين في رياضة العاب القوى على أهم المحددات النفسية والى أي مدى يعتمدونها؟ ومن هنا قدمنا إجابة أولية لهذا التساؤل والتي كان نصها كالآتي: "يوجد اطلاع مقبول للمدربين والمؤطرين على مختلف المحددات النفسية المدروسة والمعتمدة في عملية الانتقاء"، ومن أجل التأكد من صحة الفرضيات قمنا بدراسة ميدانية على المدربين المسؤولين عن عملية الانتقاء، حيث تم توزيع استبيان على عينة قدرت بـ 33 مدربا من الرابطة الجهوية لألعاب القوى جنوب-شرق، ليتم بعدها اعتماد المنهج الوصفي التحليلي، وفي الأخير تم الوصول إلى أن مستوى الاطلاع على المحددات النفسية ومراعاتها من طرف المدربين والمؤطرين في عملية الانتقاء لدى الناشئين في ألعاب القوى مقبول إلى حد ما. ........................................................................................................résumé................................................................................................. Les déterminants psychologiques à l'heure actuelle sont considérés comme une partie très importante et intégrante du processus de sélection, en particulier dans le domaine sportif, car tous les entraîneurs et ceux qui sélectionnent les joueurs doivent être bien informés des plus importants déterminants psychologiques et les prendre en compte pendant le processus à faire. Notre étude vise à déterminer la réalité de l'adoption des déterminants psychologiques dans le processus de sélection des juniors en athlétisme, Au début une problématique est soulevée comme suite: Existe-t-il des connaissances des entraîneurs et des formateurs dans le sport de l'athlétisme sur les plus importants déterminants psychologiques et dans quelle mesure en dépendent-ils? Ainsi, nous avons apporté une réponse préliminaire à cette question, qui était la suivante: «Il y a une connaissance acceptable des formateurs et des entraîneurs des différents déterminants psychologiques étudiés et validés dans le processus de sélection». Un échantillon estimé à 33 entraîneurs de l’Association Régional d’Athlétisme Sud-est, suivi par une approche analytique descriptive qui a été adoptée, et finalement il ressort que le niveau de familiarité avec les déterminants psychologiques et leur prise en compte par les entraîneurs et les formateurs dans le processus de sélection des juniors en athlétisme est quelque peu acceptable.
دراسة ميدانية على مستوى الرابطة الجهوية لألعاب القوى جنوب شرق - باتنة –